2017
DOI: 10.1002/cam4.1065
|View full text |Cite
|
Sign up to set email alerts
|

Tolcapone induces oxidative stress leading to apoptosis and inhibition of tumor growth in Neuroblastoma

Abstract: Catechol-O-methyltransferase (COMT) is an enzyme that inactivates dopamine and other catecholamines by O-methylation. Tolcapone, a drug commonly used in the treatment of Parkinson's disease, is a potent inhibitor of COMT and previous studies indicate that Tolcapone increases the bioavailability of dopamine in cells. In this study, we demonstrate that Tolcapone kills neuroblastoma (NB) cells in preclinical models by inhibition of COMT. Treating four established NB cells lines (SMS-KCNR, SH-SY5Y, BE(2)-C, CHLA-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Since this generation of ROS induces cytotoxicity and neurodegeneration, COMT, MAO, and VMAT2 play an important role in preventing dopamine oxidation in dopaminergic neurons [ 38 ]. Therefore, Tolcapone, a potent COMT inhibitor to treat Parkinson’s disease, was reported in neuroblastoma cell lines to induce oxidative stress leading to caspase-3-mediated apoptosis and to inhibit tumor proliferation [ 44 ]. The efficacy of Tolcapone in neuroblastoma cell lines was also demonstrated in the present study and showed synergy effect with VMAT2 inhibitor in MYCN-cluster representative IMR-32 cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Since this generation of ROS induces cytotoxicity and neurodegeneration, COMT, MAO, and VMAT2 play an important role in preventing dopamine oxidation in dopaminergic neurons [ 38 ]. Therefore, Tolcapone, a potent COMT inhibitor to treat Parkinson’s disease, was reported in neuroblastoma cell lines to induce oxidative stress leading to caspase-3-mediated apoptosis and to inhibit tumor proliferation [ 44 ]. The efficacy of Tolcapone in neuroblastoma cell lines was also demonstrated in the present study and showed synergy effect with VMAT2 inhibitor in MYCN-cluster representative IMR-32 cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Once the crystal structure of COMT was solved, rational design was used to create nitrocatechol inhibitors, such as entacapone and tolcapone, which contain a catechol with a nitro group at position 4 on the benzene ring [94,116]. These drugs are potent reversible inhibitors of COMT, and although their primary clinical application is as an adjunct to levodopa in Parkinson disease, RCTs have explored their effects in attention [117], cognitive deficits in schizophrenia [118], and based on tolcapone's apoptotic effects, as a chemotherapeutic in neuroblastoma [95,119].…”
Section: Drugs Used To Treat Neurological Diseasementioning
confidence: 99%
“…Moreover, nortriptyline, a tricyclic antidepressant used to treat depression, however, has antineoplastic activity in various cancers such as bladder, prostate, myeloma ( Pan et al, 2010 ; Mao et al, 2011 ; Yuan et al, 2015 ). In addition, recent studies have shown that tolcapone, a catechol-O-methyltransferase inhibitor used in Parkinson’s disease, decreases cell viability in lung cancer and neuroblastoma cell lines ( Forester and Lambert, 2014 ; Maser et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%